GEOMATICS AND CIVIL ENGINEERING INNOVATIVE RESEARCH ON HERITAGE: INTRODUCING THE “ENGINEER” PROJECT - Agapiou, Athos; Aktas, Y.; Barazzetti, L.; Christophi, Costas; Cuca, Branka; D’Ayala, D.; Kyriakides, Nicholas; Kyriakidis, Phaedon; Lysandrou, Vasiliki; Oreni, D.; Previtali, M.; Skarlatos, Dimitrios; et al. (My University, 2023)
This paper aims to introduce the concept and objectives of a recently supported European project entitled “Geomatics and Civil Engineering Innovative Research on Heritage”, in short ENGINEER. The ENGINEER project visions to enhance and extend inter- departmental multidisciplinary research activities of the Department of Civil Engineering & Geomatics of the Cyprus University of Technology through coordination and support actions as well as through targeted research activities with the support of European leading institutions. Project tasks aim to fill research multidisciplinary gaps, push, and extend knowledge into new and innovative fields dealing with the monitoring, digitization, visualization, and preservation of ancient monuments and cultural heritage sites, assisting their protection, promotion, and safeguarding.
Keywords: Geomatics; Civil Engineering; Cultural Heritage; Digitization; Documentation; Structural Engineering; Earthquake Engineering; Monuments